Avaliação do Curso de Doutorado em Economia do CAEN/UFC na perspectiva do egresso - Martins, Viviani Quinto de Azevedo (2022)
This work aims to analyze the profile of graduates of the PhD in Economics course at CAEN/UFC regarding sociodemographic aspects (academic training and salary range), and to evaluate this postgraduate program from the perspective of the graduate. For this, the descriptive quantitative approach is used from an online survey created in the Google Forms tool and made available by email and the Whatsapp application to the target audience of the research. Analyzing the data, it was observed that the majority of graduates are male, attended basic education, elementary and high school in private educational institutions, and graduation and post-graduation in public universities. Considering that a significant portion of the sample attended the master's degree at CAEN, location was the main determinant in choosing the doctoral course at CAEN by postgraduates. In terms of the labor market, it is observed that the majority of graduates work in universities as teachers and technicians, and the salary varies between R$10,000 and R$15,000. As for the evaluation of the Doctoral course, it can be inferred that most of its graduates would recommend CAEN's PhD course to other students.